Effect of estradiol cypionate and GnRH treatment on plasma estradiol-17β concentrations, synchronization of ovulation and on pregnancy rates in suckled beef cows treated with FTAI-based protocols - Uslenghi, Gastón (2016)
Two experiments were conducted to evaluate the effect of different ovulation inducers on E-17β plasma concentrations, synchronized ovulations and pregnancy rates. In Experiment 1, cows received a progesterone intravaginal device (PID) with 1 g of progesterone (P4) plus 2 mg of estradiol benzoate (EB) (day 0). At PID removal (day 8), cows received 0.150 mg of D-cloprostenol and were randomly assigned to four treatment groups (n = 10/treatment): Group ECP: 1 mg of estradiol cypionate at PID removal, Group EB: 1 mg of EB 24 hr after PID removal, Group GnRH: 10 μg of GnRH 48 hr after PID removal, Group ECP-GnRH: 1 mg of ECP at PID removal plus 10 μg of GnRH 48 hr later. Ultrasonographic examinations were performed to detect the dominant follicle and ovulation. GnRH-treated cows ovulated later (p < .05) compared to ECP- and ECP+GnRH-treated cows. There were effects of treatment, time and their interaction on E-17β concentrations (p < .05). ECP treatment affected plasma E-17β concentration, which increased earlier and decreased later compared to treatments without ECP. In Experiment 2, cows received (i) ECP: n = 126; (ii) EB: n = 126; (iii) GnRH: n = 136; (iv) ECP+GnRH: n = 139; FTAI was performed 48-50 hr after PID removal. Pregnancy rates did not differ among ovulation inducers (p > .05; ECP: 54.0%, 68/126; EB: 49.2%, 62/126; GnRH: 40.4%, 55/136; ECP+GnRH: 43.9%, 61/139). In conclusion, ECP administration (ECP and ECP+GnRH treatments) affected E-17β concentrations, determining its earlier increase and later decrease compared to treatments without ECP (EB and GnRH treatments). ECP+GnRH-treated cows achieved the best distribution of ovulations without affecting pregnancy rates.